Electrospinning alginate/polyethylene oxide and curcumin composite nanofibers - Javier, Gutierrez Gonzalez; Esther, Garcia-Cela; Magan, Naresh; Rahatekar, Sameer S. (Elsevier, 2020)
Manufacturing a sodium alginate (SA) and polyethylene oxide (PEO) composite loaded with curcumin (CU) was accomplished in this study by using electrospinning. These composite nanofibers were crosslinked using trifluoroacetic acid (TFA) mechanically characterized along with the morphological properties of the composite nanofiber mesh. We were successful in manufacturing the composite nanofibers with a wide range of CU concentrations ranging from 10 to 40 wt%. Firstly, dissolved in a saturated water/CU solution it was added to SA/PEO blending, homogenized and electrospun. Mechanical properties were affected by both CU addition and the cross-linking process, resulting in a higher ultimate tensile stress (MPa) (from 4.3±2 to 15.1±2 at 10% CU) and Young modulus (GPa) (0.0076±0.003, 0.044±0.003 before and after TFA). CU was successfully encapsulated in the SA nanofibers and excellent mechanical properties were obtained. By using a biocompatible TFA crosslinking and the natural properties of alginate this nanofiber composite could potentially be used for filtering, environmental pollution control, food packaging and for tissue engineering.
Keywords: electrospinning; sodium alginate; curcumin; nanofibers; biomedical